P11.38 The Galectin-1 inhibitor OTX-008 has antiproliferative effects on human glioblastoma cells independent of MGMT-promotor status. (6th September 2019) - Goett, H; Kolodziej, M; Pons-Kühnemann, J; Schwarm, F; Koch, C; Uhl, E; Stein, M
Abstract: BACKGROUND: The protein Galectin-1 (gal-1) is known to be involved in proliferation and progression of several malignancies. The allosteric gal-1 inhibitor OTX-008 has an antiproliferative effect on various tumors in vitro and in vivo. However, the effect of OTX-008 on patient derived GBM cultures is unknown. The aim of our study was to investigate the antiproliferative effects of OTX-008 on U87-MG and A172 cells, patient derived GBM cultures, and cultured human astrocytes (HCA). MATERIAL AND METHODS: GBM specimens from 10 patients were intraoperatively retrieved out of the 5-ALA-positive areas and were cultured in DMEM. In these cell cultures, U87-MG and A172 cell lines, and in HCA the gal-1 expression was determined by quantitative RT-PCR. Gal-1 expression below the median was defined as low-gal-1 expression (LGE), above as high-gal-1 expression (HGE). OTX-008 was administered and cell viability was assessed after 72h with MTT assay. Dose-response curves and influence of gal-1 expression were calculated by probit analysis in a logit model with logarithmic transformation of x-axis. Comparison between MGMT promotor methylated and unmethylated cells was performed using the Mann-Whitney U test. RESULTS: OTX-008 inhibited cell proliferation of all 10 patient derived GBM cell cultures with a mean ED50 of 34.28 (95% CI: 20.29- 61.57) μM and a mean ED95 of 100.90 (59.30- 199.33) μM. Antiproliferative effects of OTX-008 for U87-MG and A172 cells were found with an ED50 of 17.44 (95% CI: 13.24- 22.52) μM and 33.36 (95% CI: 24.30- 45.86) μM. In 5 cell cultures of the patient derived cells LGE and in the other 5 HGE was determined. Probit analysis showed an ED50 of 20.43 (95% CI: 16.03- 24.89) μM for the LGE group and an ED50 of 33.98 (95% CI: 28.15- 40.89) μM for the HGE-group. Between MGMT-promotor methylated and unmethylated cells no statistically significant difference for the ED50 was observed (38.36 vs. 31.56; P=0.454). Probit analysis of OTX-008 administration in HCA showed no dose-response-relation. CONCLUSION: OTX-008 has antiproliferative effects on human glioblastoma cells independent of MGMT-promotor methylation status. The sensitivity of GBM cells to OTX-008 depends on the gal-1 expression level. In HCA no effect on cell viability was observed. OTX-008 seems a promising novel substance in glioblastoma therapy.